EFFECTIVENESS OF INTERACTIVE METHODS IN IMPROVING VOCABULARY SKILLS OF PRIMARY CLASS STUDENTS (American Journal of Pedagogical and Educational Research, 2023)
In this article, we discuss the effectiveness of interactive methods in improving the vocabulary of elementary school students.